Virtual Balancing for Studying and Training Postural Control - Buettner, Daniela; Dalin, Daniela; Wiesmeier, Isabella K.; Maurer, Christoph (Frontiers in Neuroscience, 2017)
Postural control during free stance has been frequently interpreted in terms of balancing an inverted pendulum. This even holds, if subjects do not balance their own, but an external body weight. We introduce here a virtual balancing apparatus, which produces torque in the ankle joint as a function of ankle angle resembling the gravity and inertial effects of free standing. As a first aim of this study, we systematically modified gravity, damping, and inertia to examine its effect on postural control beyond the physical constraints given in the real world. As a second aim, we compared virtual balancing to free stance to test its suitability for balance training in patients who are not able to balance their full body weight due to certain medical conditions. In a feasibility study, we analyzed postural control during free stance and virtual balancing in 15 healthy subjects. Postural control was characterized by spontaneous sway measures and measures of perturbed stance. During free stance, perturbations were induced by pseudorandom anterior-posterior tilts of the body support surface. In the virtual balancing task, we systematically varied the anterior-posterior position of the foot plate where the balancing forces are zero following a similar pseudorandom stimulus profile. We found that subjects' behavior during virtual balancing resembles free stance on a tilting platform. This specifically holds for the profile of body excursions as a function of stimulus frequencies. Moreover, non-linearity between stimulus and response amplitude is similar in free and virtual balancing. The overall larger stimulus induced body excursions together with an altered phase behavior between stimulus and response could be in part explained by the limited use of vestibular and visual feedback in our experimental setting. Varying gravity or damping significantly affected postural behavior. Inertia as an isolated factor had a mild effect on the response functions. We conclude that virtual balancing may be well suited to simulate conditions which could otherwise only be realized in space experiments or during parabolic flights. Further studies are needed to examine patients' potential benefit of virtual balance training.